ANALISIS PENGARUH MERCHANDISE, STORE ATMOSPHERE, INTERAKSI ANTARA PELANGGAN DENGAN PELAYAN TOKO TERHADAP IMPULSE BUYING PADA TOKO SIRANDA - Utami, Nurul Mutya; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2015)
For this period of time, all the work Toko Siranda has performed to fullfill consumer’s need is unsucessful and the growth of mini markets in Semarang reduces sales and turnovers in Toko Siranda. This research aims to test the effect of merchandise, store atmosphere, and interaction between customers and store clerks towards impulse buying in Toko Siranda.This research uses questionnaire with 100 samples of respondent and the technique of sample's withdrawal is accidental sampling. The result of double linear regression shows that three independent variables which are merchandise (0,281), store atmosphere (0,203) and interaction between customers and store clerk (0,371) have positive relations along with dependent variables, impulse buying. The result of t test shows the each independent variables significantly influence impulse buying. Likewise , the results of the F test ( 36.795 ) shows that the three independent variables significantly influence impulse buying although the value of adjusted R square of 0,520.And the result shows impulse buying is most affected by variable of interaction between customers and store clerks. this is caused by the service provided in Toko Siranda is friendly and well mannered. The store clerks are giving great service with hospitality, well mannered and friendly towards the customers.